The composite of bone marrow concentrate and PRP as an alternative to autologous bone grafting - Hakimi, Mohssen; Grassmann, Jan-Peter; Schneppendahl, Johannes; Gehrmann, Sebastian; Hakimi, Ahmad-Reza; Kroepil, Patric; Sager, Martin; Herten, Monika; Wild, Michael; Windolf, Joachim; Jungbluth, Pascal; Betsch, Marcel (PLoS ONE, 2014)
One possible alternative to the application of autologous bone grafts represents the use of autologous bone marrow concentrate (BMC). The purpose of our study was to evaluate the potency of autologous platelet-rich plasma (PRP) in combination with BMC. In 32 mini-pigs a metaphyseal critical-size defect was surgically created at the proximal tibia. The animals were allocated to four treatment groups of eight animals each (1. BMC+CPG group, 2. BMC+CPG+PRP group, 3. autograft group, 4. CPG group). In the BMC+CPG group the defect was filled with autologous BMC in combination with calcium phosphate granules (CPG), whereas in the BMC+CPG+PRP group the defect was filled with the composite of autologous BMC, CPG and autologous PRP. In the autograft group the defect was filled with autologous cancellous graft, whereas in the CPG group the defect was filled with CPG solely. After 6 weeks radiological and histomorphometrical analysis showed significantly more new bone formation in the BMC+CPG+PRP group compared to the BMC+CPG group and the CPG group. There were no significant differences between the BMC+CPG+PRP group and the autograft group. In the PRP platelets were enriched significantly about 4.7-fold compared to native blood. In BMC the count of mononuclear cells increased significantly (3.5-fold) compared to the bone marrow aspirate. This study demonstrates that the composite of BMC+CPG+ PRP leads to a significantly higher bone regeneration of critical-size defects at the proximal tibia in mini-pigs than the use of BMC+CPG without PRP. Furthermore, within the limits of the present study the composite BMC+CPG+PRP represents a comparable alternative to autologous bone grafting. © 2014 Hakimi et al.
CRIS-Team Scopus Importer:2022-07-20